A Quick and Simple Technique for Orientating Diatoms for SEM and Light Microscopy. (January 2020) - Webber, Mark; Humphrey, Elaine
Abstract: Abstract : A method was developed to expedite the imaging of diatoms by optimizing their orientation. This quick technique puts grooves into a SEM stub so that as the diatoms are laid down they either land on the flat surface or in a variety of positions in the grooves, thereby reducing time required to capture taxonomically critical features.